Teacher education and the GERM: policy entrepreneurship, disruptive innovation and the rhetorics of reform. Issue 1 (2nd January 2019) - Ellis, Viv; Steadman, Sarah; Trippestad, Tom Are
ABSTRACT: This article addresses the question: how do a new cadre of teacher education providers in England, imbued in the discourses of the Global Education Reform Movement, construct the problem of a supposedly "failing" existing teacher education system associated with universities; what solutions to this problem do they propose and on what grounds; and how sound are their arguments? We make a rhetorical analysis of publicly available discourse from a "new rhetorical" perspective. We focus on one case in England: the Institute for Teaching (IFT), an organisation that has grown out an influential Multi-Academy Trust (MAT) and that models itself on independent Graduate Schools of Education in the USA, such as Relay. We examine the emergence of the IFT as a case of policy entrepreneurship, capitalising on a travelling policy idea to create a market for its provision of "practice"-based teacher education programmes. We show how the IFT has rhetorically constructed its policy window using typical neo-liberal, reformist explanatory frames, allowing them to present themselves as disruptive innovators capable of solving societal challenges. Although apparently sophisticated in presentation and rhetorically adept, we argue that, ultimately, the IFT's rhetoric is instead sophistic, presenting fallacious arguments in plausible ways about complex educational and social problems.